Developing a Process of Preparing Fallopia multiflora Thunb. and Proposing Basic Standards for the Product - Thi Thuong, Bui; Thanh Binh, Nguyen Thi; Xuan Sinh, Pham; Thanh Hai, Nguyen; Xuan Tung, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
Fallopia multiflora Thunb. is a precious remedy in traditional medicine of many countries. In terms of chemical composition, emodin (EM) and 2,3,5,4′-tetrahydroxystilben-2- O - β -D-glucoside (THSG) were identified as chemical markers of Fallopia multiflora Thunb. This study was conducted to develop a preparing process that helps to minimize the THSG content while increasing the ratio between EM and THSG. The HPLC-DAD method was used to quantify these substances in the raw materials and samples after each processing stage to investigate the effects of the different processing conditions. It is found that the process of preparing Fallopia multiflora Thunb. can reduce at least 53% of THSG. The ratio of EM to THSG increased by more than 2.6 times after the processing. The process has many advantages, such as simplicity, no need of soaking the herb in rice water, and short processing time. The standards with such criteria as description, identification, loss on drying, extract, and assay for the prepared product were also proposed. Keywords: Fallopia multiflora Thunb., processing mechanism, emodin, 2,3,5,4′-tetrahydroxystilben-2- O - β -D-glucoside. References [1] Ministry of Health, Vietnamese Pharmacopoeia V, Medical Publishing House, Hanoi, Part 2, 2018, pp. 1180-1181 (in Vietnamese). [2] B. T. Thuong, P. X. Sinh, N. T. Hai, N. T. T. Binh, N. X. Tung, Effect of Traditional Preparation Processing on the Total Phenol Content and Antioxidant Activity of Fallopia multiflora Thunb., VNU Journal of Science: Medical and Pharmaceutical Sciences, Vol. 36, No. 4, 2020, pp. 23-30 (in Vietnamese), https://doi.org/10.25073/2588-1132/vnumps.4264 [3] Commission Chinese Pharmacopoeia, Pharmacopoeia of the People’s Republic of China, China Medical Science and Technology Press: Beijing, China, Part I, 2015, pp. 175-177. [4] Department of Health, Hong Kong Chinese Materia Medica Standards, Hong Kong Special Administrative Region, Hong Kong, Vol. 2, 2008, pp. 223-233. [5] L. Lin, B. Ni, H. Lin, M. Zhang, X. Li, Xi. Yin, C. Qu, J. Ni, Traditional Usages, Botany, Phytochemistry, Pharmacology and Toxicology of Polygonum multiflorum Thunb.: A Review, Journal of Ethnopharmacology, Vol. 159, 2015, pp. 158-183, https://doi.org/10.1016/j.jep.2014.11.009. [6] Y. Liu, Q. Wang, J. Yang, X. Guo, W. Liu, S. Ma, S. Li, Polygonum multiflorum Thunb.: A Review on Chemical Analysis, Processing Mechanism, Quality Evaluation, and Hepatotoxicity, Frontiers in Pharmacology, Vol. 9, 2018, pp. 1-9, http://doi.org/10.3389/fphar.2018.00364. [7] Use the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human, Validation of Analytical Procedures:Text and Methodology Q2 (R1), International Conference on Harmonization, Geneva, Switzerland, 2005, pp. 6-13. [8] N. T. H. Ly, T. T. Thao, P. V. Truong, P. T. Phuong, Quality Evaluation of Fallopia multiflora in Vietnam Based on HPLC-FLD and Chemometrics, Natural Products Chemistry & Research, Vol. 6, No. 6, 2018, pp. 1-7, http://doi.org/10.4172/2329-6836.1000346. [9] P. X. Sinh, Traditional Pharmacology, Medical Publishing House, Hanoi, 2014, pp. 352-353 (in Vietnamese). [10] D. Q. Luo, P. Jia, S. S. Zhao, Y. Zhao, H. J. Liu,F. Wei, S. C. Ma, Identification and Differentiation of Polygonum multiflorum Radix and Polygoni multiflori Radix Preaparata through the Quantitative Analysis of Multicomponents by the Single Marker Method, Journal of Analytical Methods in Chemistry, Vol. 2019, 2019, pp. 1-13, https://doi.org/10.1155/2019/7430717.